Візуально-графічні особливості японських ремесел у контексті екологічного дизайну - Моравська, Валерія Андріївна; Moravska, Valeriia Andriivna (Національний університет "Львівська політехніка", 2025)
У магістерській роботі представлено теоретичні та методологічні засади дослідження, здійснено комплексний аналіз історичних, культурологічних і мистецтвознавчих джерел, що висвітлюють розвиток японських ремесел та естетичних систем. Розкрито специфіку філософсько-естетичних принципів Японії та їхній вплив на сучасні дизайнерські практики в глобальному контексті. На основі проведеного аналізу окреслено та обґрунтовано концептуальні, художньо-образні, композиційні й технологічні рішення інтеграції традиційних японських підходів у сучасний екологічний графічний дизайн. Подано результати розроблення проектних засад, що демонструють можливості адаптації японських ремісничих технік, естетики простоти та принципів матеріальної й процесуальної усвідомленості у візуальній комунікації, зокрема у дизайні друкованих та цифрових носіїв. Актуальність дослідження: 1. полягає у відсутності комплексного наукового аналізу філософсько-естетичних принципів японських ремесел у контексті графічного дизайну. Існуючі дослідження розглядають японські ремесла, естетику або екологічний дизайн переважно окремо, без інтеграції цих напрямів у цілісну систему. Це ускладнює застосування традиційних японських принципів у сучасних екологічно орієнтованих графічних практиках, які сьогодні потребують глибшої уваги до матеріальності, сталих процесів і візуальної чистоти; 2. потребі інтеграції естетичних, культурних та екологічних підходів. Аналіз японських ремесел як носіїв філософії та естетики дозволяє сформувати методологію створення графічних продуктів, що поєднують культурну спадщину з екологічною свідомістю. Традиційні техніки Японії демонструють гармонію природних матеріалів, мінімалізму та філософських уявлень про повагу до природи, що робить їх актуальними моделями 5 для сучасного сталого дизайну; 3. можливості практичного застосування японської ремісничої естетики в сучасному графічному дизайні.Дослідження філософських принципів і візуальних особливостей японських ремесел створює підґрунтя для нових дизайнерських рішень у сфері айдентики, книжкового дизайну, мультимедійних і просторових проєктів. Такий підхід дозволяє розробляти екологічно виважені та культурно змістовні візуальні системи, що відповідають вимогам сталого розвитку та сучасних естетичних тенденцій. Об?єкт дослідження: традиційні японські ремесла та їхні візуально-графічні особливості. Предмет дослідження: філософські принципи, композиційні та декоративні особливості японських ремесел, а також способи їх інтеграції у сучасний екологічний графічний дизайн для формування естетично і функціонально обґрунтованих дизайнерських рішень. Мета дослідження: вияв та розкриття філософських принципів та візуально- графічних особливостей японських ремесел та визначення шляхів їх інтеграції у сучасний екологічний графічний дизайн. Дослідження спрямоване на встановлення зв’язку між традиційною японською естетикою, ремісничими техніками та сучасними принципами дизайну. В розділі 1 проведене дослідження традиційних японських ремесел, визначено ключові терміни, які формують апарат роботи. Проаналізовано стан дослідження питання та історичний розвиток ремесел і їх вплив на формування візуальної культури. Також описано методи дослідження та сформовано джерельна база. В розділі 2 розглянуто японське уявлення про природу, вплив релігії та ідеї природності на формування ремесел. Проаналізовано етику матеріалу в традиційних ремеслах. Показано розвиток символіки, орнаментики та композиційних рішень у японській культурі. Пояснено, як естетика простоти, порожнечі та стриманості формує візуальні основи екологічного мислення. Розділ 3 аналізує сучасні підходи до екологічного графічного дизайну, розглядає, як японські техніки та візуальні принципи адаптуються в графічних дизайнерських практиках. Також пропонує методику інтеграції роботи з матеріалом 6 та стратегію екологічної комунікації, окреслює перспективи розвитку цього напрямку. Розділ 4 сконцентрований на розробці та дизайнерських рішеннях листівок та анімації. Детально описується концепція проєкту, етапи створення, ідеї та цілі. Обґрунтовано стилістичні особливості в проєктуванні листівок, описано технічні особливості і техніки виконання, які були використанні при розробці. Розділ 5 показує економічний аналіз проєкту, та розглядає економічні аспекти створення продукції. Проведено оцінку витрат та списку розроблюваних елементів. На основі кожного розділу було сформовано висновки, що окреслюють основні тези та думки досліджень.

In the master's thesis, the theoretical and methodological foundations of the research are presented, along with a comprehensive analysis of historical, cultural, and art studies sources that illuminate the development of Japanese crafts and aesthetic systems. The specificity of Japanese philosophical and aesthetic principles and their influence on contemporary design practices in a global context is revealed. Based on the conducted analysis, conceptual, artistic, compositional, and technological approaches to integrating traditional Japanese methods into contemporary ecological graphic design are identified and substantiated. The work also outlines the results of developing project-based frameworks that demonstrate the potential for adapting Japanese craft techniques, the aesthetics of simplicity, and principles of material and process awareness within visual communication, particularly in the design of printed and digital media. The relevance of the study: 1. the absence of a comprehensive scientific analysis of philosophical and aesthetic principles of Japanese crafts within the context of graphic design. Existing studies typically examine Japanese crafts, aesthetics, or ecological design separately, without integrating these dimensions into a unified conceptual system. This limits the effective application of traditional Japanese principles in contemporary environmentally oriented graphic design practices, which increasingly require attention to materiality, sustainable processes, and visual clarity; 2. the need to integrate aesthetic, cultural, and ecological approaches. An analysis of Japanese crafts as carriers of philosophical and aesthetic values enables the formation of a methodology for creating graphic products that combine cultural heritage with ecological awareness. Traditional Japanese techniques demonstrate a harmony of natural materials, minimalism, and philosophical notions of respect for nature, making them relevant models for modern sustainable design; 3. The potential for practical application of Japanese craft aesthetics in contemporary graphic design. The study of philosophical principles and visual features of 8 Japanese crafts provides a foundation for new design solutions in branding, book design, multimedia, and spatial visual systems. This approach enables the creation of ecologically conscious and culturally meaningful visual identities that align with the principles of sustainable development and current aesthetic trends. Object of the research: traditional Japanese crafts and their visual–graphic characteristics. Subject of the research: philosophical principles, compositional and decorative features of Japanese crafts, and methods of their integration into contemporary ecological graphic design to form aesthetically and functionally grounded design solutions. Purpose of the research: to identify and analyze the philosophical principles and visual–graphic characteristics of Japanese crafts and to determine the pathways for their integration into contemporary ecological graphic design. The research aims to establish the connection between traditional Japanese aesthetics, craft techniques, and modern design principles. Chapter 1 explores traditional Japanese crafts and defines the key terminology that forms the conceptual foundation of the work. The state of research and historical development of crafts and their influence on visual culture are analyzed. The research methods and the source base are also outlined. Chapter 2 examines Japanese views on nature, the influence of religion, and the idea of naturalness on the formation of crafts. The ethics of material in traditional crafts is analyzed. The development of symbolism, ornamentation, and compositional solutions in Japanese culture is explored. It is explained how the aesthetics of simplicity, emptiness, and restraint shape the visual foundations of ecological thinking. Chapter 3 analyzes contemporary approaches to ecological graphic design and considers how Japanese techniques and visual principles are adapted in modern design practices. It proposes a method for integrating material-based work and strategies for ecological communication, outlining the prospects for further development in this field. Chapter 4 focuses on the development and design solutions of the postcard series and animations. The chapter provides a detailed description of the project concept, stages of creation, ideas, and objectives. Stylistic decisions in the design of the postcards are 9 substantiated, and the technical aspects and techniques used during development are described. Chapter 5 presents the economic analysis of the project and considers the financial aspects of producing the designed materials. The cost assessment and list of developed components are provided. Based on each chapter, conclusions have been formulated, summarizing the key findings and ideas of the research.
Visual and graphic features of Japanese crafts in the context of eco-friendly design
Keywords: 8.022.00.01; японська естетика; ремесла; візуальна комунікація; екологічний дизайн; листівка; Japanese aesthetics; crafts; visual communication; ecological design; postcard